Gelatin scaffolds loaded with asiaticoside/2‐hydroxypropyl‐β‐cyclodextrin complex for use as wound dressings. (13th November 2020) - Choipang, Chasuda; Buntum, Tanawat; Chuysinuan, Piyachat; Techasakul, Supanna; Supaphol, Pitt; Suwantong, Orawan
Abstract : Gelatin (Gel) is a protein polymer obtained from the hydrolysis of collagen. Gel was used to prepare a wound dressing material loaded with asiaticoside (AC), a trisaccharide triterpene from Centella asiatica (L.) Urban commonly used in wound healing and dermis reconstruction. To improve water solubility, AC was formed into an inclusion complexation with 2‐hydroxypropyl‐β‐cyclodextrin (HPβCD) in molar ratios of 1:0.5, 1:1, and 1:2. The AC/HPβCD complexes were then loaded into a standard Gel solution and glutaraldehyde was used as the crosslinking of the Gel matrix. Freeze‐drying was used to fabricate the mixed solutions into Gel scaffolds. Average pore sizes of the scaffolds ranged between 548 and 560 μm. The compressive modulus of the scaffolds increased with increasing HPβCD molar ratio. Swelling and weight loss of the scaffolds in water increased with longer submersion times. Highest cumulative released amount of AC was obtained from the scaffold incorporated with the AC/HPβCD complex at the molar ratio of 1:2. Indirect cytotoxicity assay with human dermal fibroblasts confirmed that AC/HPβCD complex‐loaded Gel scaffolds were non‐toxic to the cells. Results demonstrated the potential of AC/HPβCD complex‐loaded Gel scaffolds for use as wound dressing materials.